Immatures of Cerambycinae (Coleoptera, Cerambycidae) collected in Litchi chinensis Sonn. (Sapindaceae) in Brazil - Casari, Sônia A.; Albertoni, Fabiano F. (Zootaxa, 2017)
Larvae and pupae of Coleoxestia waterhousei (Gounelle, 1909) (Cerambycini: Sphallotrichina) and Retrachydes thoracicus (Olivier, 1790) (Trachyderini: Trachyderina), collected in lychee trees, are described and illustrated. This is the first record of Litchi chinensis Sonn. as a host plant Retrachydes thoracicus.